2020
DOI: 10.3390/microorganisms8070978
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Extended-Spectrum β-Lactamase (ESBL) Plasmids in Enterobacteriaceae from Irrigation Water

Abstract: Extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae are classified as serious threats to human health by the U.S. Centers for Disease Control and Prevention. Water used for irrigation of fresh produce can transmit such resistant bacteria directly to edible plant parts. We screened ESBL-producing Escherichia coli, Enterobacter cloacae, and Citrobacter freundii isolated from irrigation water for their potential to transmit resistance to antibiotic-susceptible E. coli. All strains were genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…Additionally, ST131 is also frequently associated with fluoroquinolone resistance, either through the carriage of plasmid-mediated quinolone resistance (PMQR) genes such as qnrS or quinolone resistance determining region (QRDR) chromosomal mutations, such as gyrA and parC [ 14 , 17 ]. Nevertheless, ESBL dissemination can also be carried and disseminated by commensal strains through horizontal gene transfer of plasmids carrying the ESBL gene [ 18 ], as observed in community studies (e.g., [ 2 , 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ST131 is also frequently associated with fluoroquinolone resistance, either through the carriage of plasmid-mediated quinolone resistance (PMQR) genes such as qnrS or quinolone resistance determining region (QRDR) chromosomal mutations, such as gyrA and parC [ 14 , 17 ]. Nevertheless, ESBL dissemination can also be carried and disseminated by commensal strains through horizontal gene transfer of plasmids carrying the ESBL gene [ 18 ], as observed in community studies (e.g., [ 2 , 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the relatively high prevalence of ESBL observed among Enterobacterales. ESBL genes are typically borne on plasmids which are known to also carry multiple resistance genes making affected organisms multi-drug resistant [35]. The proportion of ESBL among Enterobacterales in this study was high.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study indicated in vitro transmission of ESBL-encoding multidrug-resistant (MDR) plasmids from ESBL E. coli recovered from water to susceptible E. coli making them antimicrobial-resistant (AMR) organisms (Gekenidis et al 2020). Therefore, there is a possibility that ESBL E. coli isolates which are not resistant to antibiotics phenotypically but carry ESBL-encoding genes that may be involved in horizontal transmission of ESBL-encoding genes to other bacteria in the wastewater (Lenart-Borońet al 2020).…”
Section: Introductionmentioning
confidence: 99%